Feeding dynamics and reproductive biology of the obtuse barracuda Sphyraena obtusata (Cuvier, 1829) from Ratnagiri, central west coast of India - Ranaware, Shraddha D.; Vivek H. Nirmale; Bhaskar P. Bhosale; santosh Y. Metar; Prakash E. Shingare (Indian Journal of Fisheries, 2023)
The obtuse barracuda Sphyraena obtusata (Cuvier, 1829) is a commercially important foodfish belonging to the family Sphyraenidae and landed mostly as trawl bycatch along Ratnagiri.Investigations were carried out on the species with respect to the length-weight relationship,condition factor, morphometrics, feeding and reproductive biology. The length-weightrelationship showed positive allometric growth in males, females and pooled individuals. Allmorphometric measurements showed a high degree of correlation with total length. The gutcontent analysis revealed S. obtusata to be a carnivore fish feeding mainly on fish juveniles,fish scales, crustaceans and cephalopod appendages. The male:female sex ratio was foundto be 1:0.90. Gonado-somatic index (GSI), maturity and ova diameter studies indicated thatS. obtusata has a prolonged spawning season with individuals spawning twice in a season.Absolute fecundity ranged from 68355 to 310615 eggs with an average of 137783 eggs. Themean length at sexual maturity for females was found to be 22.92 cm.Keywords:Carnivorous fish, Fish biology, Life history,Trophodynamics, Tropical fisheries